Support methodology for product quality assurance: a case study in a company of the automotive industry - Cepeda, T. A. (2019)
A visual management system aims to convert relevant information from the organization, the clients and the performance, for robust communication between all organization human resources through a set of suitable visual tools. Visual management makes part of the Lean Manufacturing methodology since it helps to highlight problems or wastes and assists in performing tasks. Among the visual management tools, the dashboard is defined as an interactive tool that presents a set of relevant information for the purpose of achieving organizational goals and strategies. The dashboard allows the monitoring and spread of relevant information to support tasks performing and decision-making. This paper presents a case study performed in an automotive company whose main objective was to simplify and standardize the collection and analysis of information concerning the product audit process, as well as improve the communication system between employees and departments involved, through the development and implementation of a dashboard. In order to achieve the intended objective, the case study involved: the definition of the information to be available in the dashboard for the audits; the development of a template to present the information briefly and clearly; identification of the necessary resources and connections for the correct operation of the dashboard (with real-time updates); definition of the process of information collecting and analysis, and the consequent connection with the problem solving process. The implementation of the dashboard allowed an increase in the reliability of the results and a significant reduction in the steps to analyze the data and, consequently, in their duration. In this way, the dashboard simplified and improved decision-making process and created a conducive environment for the departments involved in the quality audit process to perform the associated tasks.